Field-deployable, lyophilized cell-free biosensor for robust and selective detection of inorganic arsenic in complex seaweed matrices - Da-Sol Jeong; Taeok Kim; Minseok Cha; Hyewon Lee; Soo-Jung Kim (Food Research International, 2026)

Nu class glutathione S-transferase (GST) from the freshwater diatom Fragilaria saxoplanctonica: characterization and transcriptional responses to pollutant-induced oxidative stress - Jin-Joo Hong; Han-Sol Kim; Taehee Kim; Jang-Seu Ki (Molecular & Cellular Toxicology, 2026)

pH changes differently affect carbonic anhydrases (Ap-CAs) transcriptions in the marine toxic dinoflagellate Alexandrium pacificum - Han-Sol Kim; Jeongmin Shin; Taehee Kim; Jang-Seu Ki (Marine Environmental Research, 2026)

In vitro storage under slow growth, plant regeneration, and ex vitro acclimatization of Ligusticum officinale (Makino) Kitag - Ye-Won Kim; Han-Sol Lee; Hosakatte Niranjana Murthy; Hyoshin Lee; So-Young Park (South African Journal of Botany, 2026)

In vitro propagation of Cymbidium ‘Snow Pearl’ in semi-solid, liquid, and temporary immersion bioreactor system (TIS) cultures - Beomsoo Kang; Ye-Won Kim; Han-Sol Lee; Jong-Eun Han; Hosakatte Niranjana Murthy; Yae Jin Kim; Pil Man Park; So-Young Park (Horticulture, Environment, and Biotechnology, 2026)

Evaluation of two novel superoxide dismutases (SODs) from the freshwater diatom Fragilaria saxoplanctonica and their specific responses to metals and pesticides - Hee-Jin Kang; Han-Sol Kim; Taehee Kim; Jang-Seu Ki (Ecotoxicology, 2026)

Iron availability modulates ferric reduction oxidase (FRO) gene expression in the toxic dinoflagellate Alexandrium pacificum - Quynh Thi Nhu Bui; Han-Sol Kim; Sofia Abassi; Hee-Jin Kang; Jang-Seu Ki (European Journal of Protistology, 2026)

Circadian-dependent UV-B stress responses reveal differential antioxidant and photoprotective mechanisms in Achyranthes japonica microgreens - Ye Lin Kim; Han-Sol Sim; Jae Gil Yun; Ki-Ho Son (Molecular & Cellular Toxicology, 2026)

Multi-functional roles of cold shock protein genes (CSPs) in the toxic marine dinoflagellate Alexandrium catenella: assessment of cold, heat, and metal stress - Quynh Thi Nhu Bui; Han-Sol Kim; Jang-Seu Ki (Journal of Applied Phycology, 2026)

Effects of light-emitting diode (LED) light sources on in vitro protocorm-like body (PLB) proliferation, plantlet regeneration, and ex vitro acclimatization in Cymbidium ‘Snow Pearl’ - Beomsoo Kang; Ye-Won Kim; Han-Sol Lee; Jong-Eun Han; Hosakatte Niranjana Murthy; Yae Jin Kim; Pil Man Park; So-Young Park (Horticulture, Environment, and Biotechnology, 2026)

Specificity of polyclonal oligopeptide antisera targeting glycoprotein hormones from the Japanese Eel (Anguilla japonica) - Hyun-Sol Jo; Tae-Ha Kim; Jae Man Lee; Young Chang Sohn; Tae-Won Goo; Sun-Mee Hong (Biotechnology Letters, 2026)

Exploring Cyclo (-Gly-Pro) for inflammation modulation in atopic dermatitis: a study on streptococcal postbiotics - Haeun Lee; Yunseok Oh; Tae-Won Seo; Young-Bong Choi; Sol Kim; Sejin Cheon; Dong-Geol Lee; Seunghyun Kang; Kyudong Han; Young Mok Heo; Seyoung Mun (Genes & Genomics, 2026)

Enhancing methane production from swine manure through stepwise integration of food waste co-digestion, powdered activated carbon, and low voltage stimulation - Tae-Hoon Kim; Yun-Ju Jeon; Eun-Sol Kim; Yeo-Myeong Yun (Process Safety and Environmental Protection, 2026)

Comparison of deep learning models for 3D food printing monitoring system - Eunji Ju; Jaehwi Seol; Sarang Kim; Sol Kim; Soo-Jung Kim; Hyoung Il Son (Journal of Food Engineering, 2026)

Saxitoxin biosynthesis genes in the marine dinoflagellate Gymnodinium: Transcriptomes of toxic and non-toxic species and their environmental insights - Buhari Lawan Muhammad; Han-Sol Kim; Taehee Kim; Jang-Seu Ki (Harmful Algae, 2026)

Biological upcycling of conditionally biodegradable plastics: enzymatic depolymerization to microbial valorization and consolidated bioprocessing frameworks - Yunhee Jeong; Sol Min Han; Jieun Wu; KwangYoung Park; Yunjeong Song; Yung-Hun Yang; Kyung-Jin Kim; Jungoh Ahn; Kyungmoon Park; See-Hyoung Park; Si Jae Park; Eun Ju Yun; et al. (Systems Microbiology and Biomanufacturing, 2026)

Lyophilization of pharmaceuticals: an overview and practical approaches for developing the lyophilization cycle - Seon-Kwang Lee; Eun-Sol Ha; Heejun Park; Ji-Su Jeong; Chang Yell Shin; Jeong-Soo Kim; Seong Hoon Jeong; Min-Soo Kim (Journal of Pharmaceutical Investigation, 2026)

The marine water flea Diaphanosoma celebensis as an emerging model for ocean health research: A review - Duck-Hyun Kim; Jin-Sol Lee; Min-Sub Kim; Zhou Yang; Atsushi Hagiwara; Jae-Seong Lee (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

A review of ammonia toxicity on aquatic organisms: Species-specific responses, microbial shifts, and environmental interactions - Seong Chan Yun; Haksoo Jeong; Jin-Sol Lee; Jin-Hyoung Kim; Il-Chan Kim; Piotr Maszczyk; Zhou Yang; Atsushi Hagiwara; Jae-Seong Lee (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Transcriptional Regulation of Temperature-Responsive Flowering in Arabidopsis - Yun-Young Choi; Kyung-Ho Park; Sol-Bi Kim; Jae-Hoon Jung (Journal of Plant Biology, 2026)

Distribution and correlation of trace elements in Eurasian otters (Lutra lutra) from South Korea - Da Sol Park; Eun Jae Park; Dahye Shin; Rihyun Kim; Bongkyun Kim; Yongsun Hyun; Hee-Jong Kim; Kyu-Vin Kim; Chang Uk Chung; Dong-Hyuk Jeong; Jong Seung Kim; Ju Yeong Park; et al. (Environmental Science and Pollution Research, 2026)

A novel quantitative analysis method for printability in 3D food printing for surimi - Sol Kim; Jaehwi Seol; Eunji Ju; Jeonghyeon Pak; Hyoung Il Son; Soo-Jung Kim (Journal of Food Engineering, 2026)

Bacteriophage emulsion for prevention of Salmonella contamination in eggshells - Su Jin Jo; Sang Guen Kim; Sib Sankar Giri; Sung Bin Lee; Jae Hong Park; Mae Hyun Hwang; Da Sol Park; Eun Jae Park; Se Chang Park (International Journal of Food Microbiology, 2026)

Microsatellite markers reveal genetic differentiation and relationship between local populations of Korean and Holstein cattle - Sol-Song Kim; Song-Hyok Kim; Un-Hyang Ho; Sam-Rang Song; Thae-Gwang Ok; Song-Hyok Pak; Tong-Su Ho; Myong-Sik Ho (Tropical Animal Health and Production, 2025)

Virucidal activity of Cannabis sativa L. (hemp) root and stem extracts against Japanese encephalitis virus: role of stigmasterol - Han-Sol Ryu; Ki-Hyun Kim; Kiu-Hyung Cho; Ah-Ra Lee; Sang-Uk Seo; Sejin Jeon; Sun-Woo Yoon; Sanghyun Lee; Yun Kwon; Yo Han Jang (Archives of Virology, 2025)

Robust Relative Space Motion Control of Underwater Vehicles Using Time Delay Estimation - Gun Rae Cho; Hyungjoo Kang; Min-Gyu Kim; Sungho Park; Chulhee Bae; Han-Sol Jin; Seongho Jin; Ji-Hong Li (Journal of Marine Science and Engineering, 2025)
This paper presents a robust trajectory-tracking control framework for underwater vehicles operating in a relative coordinate system. Unlike conventional methods that define trajectories in the world frame, the proposed approach formulates the control problem directly in a moving reference frame, enabling accurate motion control with respect to dynamic and drifting objects affected by environmental disturbances such as ocean currents and waves. This relative-space formulation is particularly advantageous for tasks including diver guidance, floating-object inspection, and docking, where the reference itself is nonstationary. A coordinate transformation is introduced to consistently express the vehicle dynamics in the relative frame. Based on the transformed dynamics, a Time Delay Control (TDC) law is applied to estimate unmodeled dynamics and external disturbances without requiring precise system parameters. Theoretical stability analysis shows that the stability condition of the proposed controller is consistent with that of conventional TDC, allowing similar gain-tuning procedures. Simulation results demonstrate that the proposed controller achieves robust and smooth trajectory tracking even when the reference frame undergoes motion induced by ocean currents.

Effect of Illicium verum Hook.f. (star anise) extract on the modulation of systemic and mucosal immunity in Aeromonas hydrophila-aggravated Cyprinus carpio - Sib Sankar Giri; Hyoun Joong Kim; Subrata Saha; Jae Hong Park; Sung Bin Lee; Su Jin Joo; Mae Hyun Hwang; Da Sol Park; Eun Jae Park; Kihae Ra; Sukumaran Venkatachalam; Se Chang Park (Fish & Shellfish Immunology, 2025)

Thermodynamic evaluation of lithium recovery and freshwater production by sustainable hydrate-based desalination from brine solutions - Sol Geo Lim; Chang Yeop Oh; Hye Rim Choi; Donghyun Moon; Chiho Sung; Sun Ha Kim; Kongtae Ra; Minjun Cha; Ji-Ho Yoon (Desalination, 2025)

Ultralow interface resistance in porous transport electrode for efficient polymer electrolyte membrane water electrolysis at low Ir loading - Jegon Lee; Sol Kim; Jin Young Kim; Jong Hyun Jang; Hee-Young Park; Bora Seo (Chemical Engineering Journal, 2025)

Enhanced oral bioavailability of pranlukast by preparing amorphous solid dispersion via hot-melt extrusion - Dong-Hyeon Ha; Eun-Sol Ha; Heejun Park; Seon-Kwang Lee; Ji-Su Jeong; Hui-Taek Kang; Kyu-Tae Kang; In-hwan Baek; Min-Soo Kim (Journal of Pharmaceutical Investigation, 2025)

Fundamental study on the dose-effect relationship of urease inhibitors for ammonia reduction and methane recovery in simulated swine urine - Yun-Ju Jeon; Tae-Hoon Kim; Eun-Sol Kim; Seoktae Kang; Hyojeon Kim; Siyoung Seo; Yeo-Myeong Yun (Journal of Environmental Chemical Engineering, 2025)

Sustainable media development for cultured meat: Technology and material reviews - Da-Mi Choi; Sol-Hee Lee; Hack-Youn Kim (Food Research International, 2025)

Thermally induced surface-Cu-enriched NiCuOx electrocatalysts for stable ammonia oxidation to nitrite toward hydrogen production - Sol A Lee; Jiwoo Lee; Jaehyun Kim; Woo Seok Cheon; Tae Hyung Lee; Sungkyun Choi; Sang Hyun Ahn; Soo Young Kim; Jungwon Park; Ho Won Jang (Chemical Engineering Journal, 2025)

Two chloroplast superoxide dismutase genes (MnSOD and CuZnSOD) in the freshwater dinoflagellate Palatinus apiculatus and their high-level gene expression in response to algicidal agents - Quynh Thi Nhu Bui; Han-Sol Kim; Jang-Seu Ki (Journal of Applied Phycology, 2025)

Transcriptomic comparison unveils saxitoxin biosynthesis genes in the marine dinoflagellate Gymnodinium catenatum - Buhari Lawan Muhammad; Han-Sol Kim; Quynh Thi Nhu Bui; Jang-Seu Ki (Harmful Algae, 2025)

WITHDRAWN: Nutritional composition and feasibility to realize as elder-friendly food of Kola nut - Dah-Sol Kim; Soo Hyun Kim; Nami Joo; Ju Hong Park (Food and Humanity, 2025)

A novel procedure for estimating energy digestibility of feedstuffs fed to pigs - Su A Lee; Chan Sol Park; Beob Gyun Kim (Animal Feed Science and Technology, 2025)

Assessment of ship hull-attached marine diatoms: species composition and reattachment - Jaeyeong Park; Buhari Lawan Muhammad; Taehee Kim; Quynh Thi Nhu Bui; Han-Sol Kim; Kyoungsoon Shin; Bonggil Hyun; Jung-Hoon Kang; Jang-Seu Ki (Marine Pollution Bulletin, 2025)

Evaluating nuclear (18S, ITS, and 28S) and chloroplast (psbB, psbC, rbcL, and tufA) genes of the green algae Monoraphidium (Sphaeropleales, Chlorophyta) for DNA barcoding - Ha-Eun Lee; Taehee Kim; Han-Sol Kim; Ok-Min Lee; Jang-Seu Ki (Algae, 2025)
The genus Monoraphidium is a green microalgae distributed globally in freshwater ecosystems, and it is difficult to classify morphologically. Molecular genetic markers have been used for their taxonomy, although they have not been thoroughly evaluated. Here, we investigated three nuclear rRNA molecules (18S, internal transcribed spacer [ITS] + 5.8S, and 28S) and four chloroplast genes (psbB, psbC, rbcL, and tufA) using 16 Monoraphidium strains consisting of 9 species. Upon comparisons of genetic diversity and marker performance evaluation, we found that ITS was the best marker for Monoraphidium to discriminate each species, followed by tufA. The taxonomic discrimination power of the ITS was supported by the neighbor-joining tree. In addition, a secondary structure of ITS2 combined with compensatory base changes showed the distinct differences among individual species of Monoraphidium. These suggest that ITS may be the best marker for species differentiation of the coccoid green algae Monoraphidium.

Nitrogen (N) balancing metabolism in the toxic dinoflagellate Alexandrium pacificum against N shift revealed by physiology and N-related genes regulation - Han-Sol Kim; Sofia Abassi; Quynh Thi Nhu Bui; Jang-Seu Ki (Chemosphere, 2025)

Experimental and computational insights into sustainable lithium recovery and freshwater production via CO2 hydrate-based desalination - Sol Geo Lim; Donghyun Moon; Chang Yeop Oh; Hye Rim Choi; Chiho Sung; Sun Ha Kim; Kongtae Ra; Minjun Cha; Ji-Ho Yoon (Chemical Engineering Journal, 2025)

Photosynthesis genes modulate cadmium tolerance in the freshwater alga Closterium acutum revealed by transcriptome analysis - Jeongmin Shin; Han-Sol Kim; Quynh Thi Nhu Bui; Taehee Kim; Jang-Seu Ki (Journal of Applied Phycology, 2025)

Using a passive solar greenhouse with water tanks in overwintering of juvenile sea cucumber Apostichopus japonicus - Sol-Yon Kim; Yon-Mi Kim; Chol-Ho An; Jin-Myong Ro; Ryong-Un Kim; Jun-Sok Kim (Aquacultural Engineering, 2025)

Comprehensive review in continuous direct compression process - Mi-Seon Na; Yeon Sil Lee; Eun-Sol Ha; Min-Soo Kim; Heejun Park (Journal of Pharmaceutical Investigation, 2025)

Scalable electrodeposition method to construct zincophilic 3D Cu nanosheet current collector for Zn metal anode - Da-Eun Hyun; Jong Chan Choi; Jae Sol Sim; Ki Beom Kim; Yoon Ho Kim; Dae Soo Jung; Yun Chan Kang (Chemical Engineering Journal, 2025)

Occurrence and distribution of brominated and fluorinated persistent organic pollutants in surface sediments focusing on industrially affected rivers - Sol Choi; Okon Dominic Ekpe; Fulgence Jacob Macha; Wonjin Sim; MinGyeong Kim; Mikyung Lee; Jeong-Eun Oh (Chemosphere, 2025)

Scalable fabrication of a tough and recyclable spore-bearing biocomposite thermoplastic polyurethane - Han Sol Kim; Evan M. White; Grant Crane; Kush Patel; Myung Hyun Noh; Md Arifur Rahman; Adam M. Feist; Jason J. Locklin; Jonathan K. Pokorski (Chemical Engineering Journal, 2025)

Adverse effects of environmentally relevant microplastics on in vivo endpoints, oxidative stress, and mitogen-activated protein kinase signaling pathway and multixenobiotic resistance system in the marine rotifer Brachionus plicatilis - Wajid Ali; Haksoo Jeong; Duck-Hyun Kim; Jin-Sol Lee; Philippe Zinck; Sami Souissi; Jae-Seong Lee (Science of The Total Environment, 2025)

Efficacy of Bone Regeneration Cell Therapy Using Mesenchymal Stem Cells Originating from Embryonic Stem Cells in Animal Models; Bone Defects and Osteomyelitis - Jin-Ho Park; Han-Sol Bae; Ingeun Kim; Jiwoon Jung; Yoonho Roh; Dongbin Lee; Tae Sung Hwang; Hee-Chun Lee; June-Ho Byun (Tissue Engineering and Regenerative Medicine, 2025)

Evaluation of acute, repeated dose 28-day and 13-week oral toxicity and genotoxicity of a standardized fraction (HemoHIM) from Angelica gigas, Cnidium officinale, and Paeonia lactiflora - Ju Gyeong Kim; Su-Bin Bak; Gyoung-Deuck Kim; Han-Sol Choi; Da-Ae Kwon; Ha-Young Kim; Dong-Won Son; Jang-Hun Jeong; Byung-Woo Lee; Hyo-Jin An; Hak Sung Lee (Toxicological Research, 2025)
HemoHIM is a functional food ingredient comprising a triple herbal combination of extracts from Angelica gigas Nakai, Cnidium officinale Makino, and Paeonia lactiflora Pallas. It was developed to aid the recovery of impaired immune function. Although it is widely used to treat various immune disorders in Korea, its potential toxicity has not been extensively investigated. Therefore, a comprehensive study was conducted to assess the safety of HemoHIM, including acute oral dose toxicity, 28-day and 13-week repeated-dose toxicity, and genotoxicity. To evaluate its safety profile, the dose was increased to 2,000 mg/kg/day, which corresponds to the dose limit for acute toxicity as per the Organization for Economic Cooperation and Development Test Guideline 423. No abnormal findings were observed at the higher doses. For the 28-day and 13-week repeated-dose toxicity studies, HemoHIM was administered at doses of 500, 1,000, and 2,000 mg/kg/day to examine subchronic toxicity in male and female rats. No test item-related clinical signs or mortality was observed at any of the tested doses. Gross pathology, hematology, blood chemistry, and histopathology evaluations further supported the safety of HemoHIM. Therefore, the NOAEL of HemoHIM was considered to be at 2,000 mg/kg/day for both sexes of rats. Bacterial reverse mutation tests, a chromosome aberration test in human peripheral blood lymphocytes, and a mouse micronucleus test were conducted to determine the genotoxicity of HemoHIM, which revealed that HemoHIM was non-mutagenic and non-clastogenic. Collectively, these findings provide valuable evidence to support the safe use of HemoHIM as a functional food ingredient.

Size-dependent toxicity of nano- and microplastics with zinc oxide nanoparticles in the marine rotifer Brachionus koreanus - Eunjin Byeon; Paweena Sanpradit; Jin-Sol Lee; Haksoo Jeong; Min-Sub Kim; Mi-Song Hong; Saranya Peerakietkhajorn; Alaa El-Din H. Sayed; Jae-Seong Lee (Marine Pollution Bulletin, 2024)

Differential susceptibility to hypoxia in hypoxia-inducible factor 1-alpha (HIF-1α)-targeted freshwater water flea Daphnia magna mutants - Yoseop Lee; Eunjin Byeon; Jin-Sol Lee; Piotr Maszczyk; Hyung Sik Kim; Alaa El-Din H. Sayed; Zhou Yang; Jae-Seong Lee; Duck-Hyun Kim (Marine Pollution Bulletin, 2024)

Adlercreutzia faecimuris sp. nov., producing propionate and acetate isolated from mouse feces - Min Kuk Suh; Jong- Sik Jin; Hyo Eun Do; Ji-Sun Kim; Mi Kyung Eom; Han Sol Kim; Jung- Sook Lee (Antonie van Leeuwenhoek, 2024)

Phocaeicola acetigenes sp. nov., producing acetic acid and iso-butyric acid, isolated faeces from a healthy human - Hyo Eun Do; Young Bong Ha; Ji-Sun Kim; Min Kuk Suh; Han Sol Kim; Mi Kyung Eom; Ju Huck Lee; Seung-Hwan Park; Se Won Kang; Dong Ho Lee; Hyuk Yoon; Je Hee Lee; et al. (Antonie van Leeuwenhoek, 2024)

Jatrophihabitans cynanchi sp. nov., isolated from rhizosphere soil of Cynanchum wilfordii - Min Kuk Suh; Ji-Sun Kim; Mi Kyung Eom; Han Sol Kim; Hyo Eun Do; Yong Kook Shin; Jung- Sook Lee (Antonie van Leeuwenhoek, 2024)

Genome-wide identification of 769 G protein–coupled receptor (GPCR) genes from the marine medaka Oryzias melastigma - Duck-Hyun Kim; Min-Sub Kim; Jin-Sol Lee; Deok-Seo Yoon; Jae-Seong Lee (Marine Pollution Bulletin, 2024)

Full Coverage Path Planning for Torpedo-Type AUVs’ Marine Survey Confined in Convex Polygon Area - Ji-Hong Li; Hyungjoo Kang; Min-Gyu Kim; Mun-Jik Lee; Han-Sol Jin (Journal of Marine Science and Engineering, 2024)
In this paper, we present a full coverage path planning (CPP) algorithm for the marine surveys conducted in the convex polygon shaped search area. The survey is supposed to carry out by torpedo-type AUVs (autonomous underwater vehicles). Due to their nonholonomic mechanical characteristics, these vehicles have nonzero minimum turning radius. For any given polygon shaped search area, it can always be partitioned into one or more convex polygons. With this in mind, this paper proposes a novel search algorithm called CbSPSA (Calculation based Shortest Path Search Algorithm) for full coverage of any given convex polygon shaped search area. By aligning the search inter-tracks alongside the edge with the minimum height, we can guarantee the minimum number of the vehicle’s turns. In addition, the proposed method can guarantee the planned path is strictly located inside the polygon area without overlapped or crossed path lines, and also has the total path length as short as possible. Considering the vehicle’s nonzero minimum turning radius, we also propose a sort of smoothing algorithm which can smooth the waypoint path searched by CbSPSA so that the vehicle can exactly follow it. The smoothed path is also guaranteed to be strictly located inside the polygon. Numerical simulation analyses are also carried out to verify the effectiveness of the proposed schemes.

Oxidative stress-mediated deleterious effects of hypoxia in the brackish water flea Diaphanosoma celebensis - Yoseop Lee; Duck-Hyun Kim; Jin-Sol Lee; Min-Chul Lee; Hyung Sik Kim; Piotr Maszczyk; Yoshitaka Sakakura; Zhou Yang; Atsushi Hagiwara; Heum Gi Park; Jae-Seong Lee (Marine Pollution Bulletin, 2024)

TRPM7 Mediates Neuropathic Pain by Activating mTOR Signaling in Astrocytes after Spinal Cord Injury in Rats - In Yi Kim; Chan Sol Park; Kyung Jin Seo; Jee Youn Lee; Tae Young Yune (Molecular Neurobiology, 2024)

Toxicity and speciation of inorganic arsenics and their adverse effects on in vivo endpoints and oxidative stress in the marine medaka Oryzias melastigma - Eunjin Byeon; Haksoo Jeong; Min-Sub Kim; Seong Chan Yun; Jin-Sol Lee; Min-Chul Lee; Jin-Hyoung Kim; Alaa El-Din Hamid Sayed; Jun Bo; Hyung Sik Kim; Chulho Yoon; Atsushi Hagiwara; et al. (Journal of Hazardous Materials, 2024)

Enhanced oxygen evolution reaction of 2-dimensional metal-organic frameworks with tunable nitrogen functionalities by ion beam sputtering - Woo Seok Cheon; Jeewon Bu; Sunghoon Jung; Jun-Yeong Yang; Sungkyun Choi; Jaehyun Kim; Ji Hyun Baek; Sohyeon Park; Min Kyung Lee; Sang Eon Jun; Sung Hyuk Park; Hoonkee Park; et al. (Chemical Engineering Journal, 2024)

Significant Reduction of Photosynthesis in the Harmful Dinoflagellate Margalefidinium polykrikoides by Co-culturing with the Marine Green Alga Tetraselmis suecica - Han-Sol Kim; Buhari Lawan Muhammad; Jang-Seu Ki (Ocean Science Journal, 2024)

Promoter regions of sxtA and sxtG reveal relationship between saxitoxin biosynthesis and photosynthesis in toxic Alexandrium catenella - Han-Sol Kim; Quynh Thi Nhu Bui; Jeongmin Shin; Hui Wang; Jang-Seu Ki (Journal of Applied Phycology, 2024)

Combined exposure to hypoxia and nanoplastics leads to negative synergistic oxidative stress-mediated effects in the water flea Daphnia magna - Yoseop Lee; Duck-Hyun Kim; Jin-Sol Lee; Hyung Sik Kim; Piotr Maszczyk; Minghua Wang; Zhou Yang; Da-Zhi Wang; Jae-Seong Lee (Marine Pollution Bulletin, 2024)

Toxic effects of triclosan in aquatic organisms: A review focusing on single and combined exposure of environmental conditions and pollutants - Jin-Sol Lee; Jae-Seong Lee; Hyung Sik Kim (Science of The Total Environment, 2024)

Polyphyletic origin of saxitoxin biosynthesis genes in the marine dinoflagellate Alexandrium revealed by comparative transcriptomics - Quynh Thi Nhu Bui; Han-Sol Kim; Jang-Seu Ki (Harmful Algae, 2024)

Development of saxitoxin biosynthesis gene sxtB-targeted qPCR assay for the quantification of toxic dinoflagellates Alexandrium catenella (group I) and A. pacificum (group IV) occurring in the Korean coast - Han-Sol Kim; Taehee Kim; Jaeyeon Park; Tae Gyu Park; Jang-Seu Ki (Harmful Algae, 2024)

Nuclear genome of dinoflagellates: Size variation and insights into evolutionary mechanisms - Hui Wang; Peiling Wu; Lu Xiong; Han-Sol Kim; Jin Ho Kim; Jang-Seu Ki (European Journal of Protistology, 2024)

Two novel glutathione S-transferase (GST) genes in the toxic marine dinoflagellate Alexandrium pacificum and their transcriptional responses to environmental contaminants - Hyunjun Park; Han-Sol Kim; Sofia Abassi; Quynh Thi Nhu Bui; Jang-Seu Ki (Science of The Total Environment, 2024)

Single and combined effects of increased temperature and methylmercury on different stages of the marine rotifer Brachionus plicatilis - Haksoo Jeong; Eunjin Byeon; Jin-Sol Lee; Hyung Sik Kim; Alaa El-Din H. Sayed; Jun Bo; Minghua Wang; Da-Zhi Wang; Heum Gi Park; Jae-Seong Lee (Journal of Hazardous Materials, 2024)

Combined effects of nanoplastics and elevated temperature in the freshwater water flea Daphnia magna - Paweena Sanpradit; Eunjin Byeon; Jin-Sol Lee; Haksoo Jeong; Hyung Sik Kim; Saranya Peerakietkhajorn; Jae-Seong Lee (Journal of Hazardous Materials, 2024)

Gordonibacter faecis sp. nov., producing urolithin C from ellagic acid, isolated from feces of healthy Korean subjects - Han Sol Kim; Ji-Sun Kim; Min Kuk Suh; Mi Kyung Eom; Hyo Eun Do; Ju Huck Lee; Seung-Hwan Park; Se Won Kang; Dong Ho Lee; Hyuk Yoon; Je Hee Lee; Jung-Sook Lee (Archives of Microbiology, 2024)

Isolation, culture of protoplasts of Angelica gigas Nakai and regeneration of plants via somatic embryogenesis - Han-Sol Lee; Jong-Eun Han; Eun Yee Jie; Suk Weon Kim; Hyuk Joon Kwon; Gun-Myung Lee; Hak Sung Lee; Hosakatte Niranjana Murthy; So-Young Park (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

TRPM7 Mediates BSCB Disruption After Spinal Cord Injury by Regulating the mTOR/JMJD3 Axis in Rats - Chan Sol Park; Jee Youn Lee; Kyung Jin Seo; In Yi Kim; Bong Gun Ju; Tae Young Yune (Molecular Neurobiology, 2024)

CO2 competes with radioactive chemicals for freshwater recovery: Hydrate-based desalination - Sol Geo Lim; Chang Yeop Oh; Sun Ha Kim; Kongtae Ra; Ji-Ho Yoon (Journal of Hazardous Materials, 2024)

Phenolic compounds in the freshwater environment in South Korea: Occurrence and tissue-specific distribution - Da-Hye Kim; Sol Choi; Jaeyeon Park; Kyungtae Kim; Jeong-Eun Oh (Science of The Total Environment, 2023)

Air-type photovoltaic thermal (PVT) system connected to heat recovery ventilators installed in typical classroom - Jae-Sol Choi; Gi-Cheol Kim; Min-Seok Oh; Eui-Jong Kim (Energy and Buildings, 2023)

Synergistic toxic mechanisms of microplastics and triclosan via multixenobiotic resistance (MXR) inhibition–mediated autophagy in the freshwater water flea Daphnia magna - Jin-Sol Lee; Yunmoon Oh; Hae Eun Park; Jae-Seong Lee; Hyung Sik Kim (Science of The Total Environment, 2023)

Ultrasensitive monoclonal antibodies specific to thermal stable-soluble proteins of buckwheat - Sol-A Kim; Sazzad Hossen Toushik; Jeong-Eun Lee; Won-Bo Shim (Food Chemistry, 2023)

Bioinspired synthesis of micelle-templated ultrathin silica-layered mesoporous nanoparticles with enhanced mass transfer and stability for biocatalysis - Ae Sol Lee; Kyeong Rok Kim; Joo Hyun Kim; Byung Hoon Jo; Young Hoon Song; Jeong Hyun Seo; Hye Ryoung Heo; Chang Sup Kim (Chemical Engineering Journal, 2023)

Physiological effects and molecular response in the marine rotifer Brachionus plicatilis after combined exposure to nanoplastics and copper - Chuxin Wang; Haksoo Jeong; Jin-Sol Lee; Piotr Maszczyk; Alaa El-Din H. Sayed; Un-Ki Hwang; Hyung Sik Kim; Jae-Seong Lee; Eunjin Byeon (Marine Pollution Bulletin, 2023)

Target Tracking from Weak Acoustic Signals in an Underwater Environment Using a Deep Segmentation Network - Won Shin; Da-Sol Kim; Hyunsuk Ko (Journal of Marine Science and Engineering, 2023)
In submarine warfare systems, passive SONAR is commonly used to detect enemy targets while concealing one’s own submarine. The bearing information of a target obtained from passive SONAR can be accumulated over time and visually represented as a two-dimensional image known as a BTR image. Accurate measurement of bearing–time information is crucial in obtaining precise information on enemy targets. However, due to various underwater environmental noises, signal reception rates are low, which makes it challenging to detect the directional angle of enemy targets from noisy BTR images. In this paper, we propose a deep-learning-based segmentation network for BTR images to improve the accuracy of enemy detection in underwater environments. Specifically, we utilized the spatial convolutional layer to effectively extract target objects. Additionally, we propose novel loss functions for network training to resolve a strong class imbalance problem observed in BTR images. In addition, due to the difficulty of obtaining actual target bearing data as military information, we created a synthesized BTR dataset that simulates various underwater scenarios. We conducted comprehensive experiments and related discussions using our synthesized BTR dataset, which demonstrate that the proposed network provides superior target segmentation performance compared to state-of-the-art methods.

Effects of nitrate on the saxitoxins biosynthesis revealed by sxt genes in the toxic dinoflagellate Alexandrium pacificum (group IV) - Sofia Abassi; Han-Sol Kim; Quynh Thi Nhu Bui; Jang-Seu Ki (Harmful Algae, 2023)

Simultaneous determination of 11 nootropic substances potentially adulterated in dietary supplements for improving brain function using ultra-performance liquid chromatography and liquid chromatography–quadrupole-time-of-flight mass spectrometry - Nam Sook Kim; Hwan Seong Choi; Sol A Yeon; Hyemin Bae; Hyungil Kim; Cho Sooyeul (Food Additives & Contaminants: Part A, 2023)

Data-to-data translation-based nowcasting of specific sea fog using geostationary weather satellite observation - Yerin Kim; Han-Sol Ryu; Sungwook Hong (Atmospheric Research, 2023)

In-situ desulfurization using porous Ca-based materials for the oxy-CFB process: A computational study - Eun Sol Go; Beom-Sik Kim; Jester Lih Jie Ling; Seung Seok Oh; Hyun Jun Park; See Hoon Lee (Environmental Research, 2023)

Disturbance observer-based nonfragile fuzzy tracking control of a spacecraft - Tae Joon Han; Han Sol Kim (Advances in Space Research, 2023)

Effects of dietary glycerol supplementation on meat quality, palatability, and lipid metabolism gene expression in the longissimus thoracis of Hanwoo steers - Dilla Mareistia Fassah; Hyeok Joong Kang; Seok-Hyeon Beak; Da Jin Sol Jung; Inhyuk Jeong; Sang Weon Na; Seon Pil Yoo; Soo Jong Hong; Hyun Jin Kim; Md. Najmul Haque; Hyun Jung Lee; Cheorun Jo; et al. (Meat Science, 2023)

Sustainable freshwater recovery from radioactive wastewater by gas hydrate formation - Sol Geo Lim; Chang Yeop Oh; Jong-Won Lee; Minjun Cha; Sun Ha Kim; Kongtae Ra; Kyoungkeun Yoo; Ji-Ho Yoon (Chemical Engineering Journal, 2023)

Molecular cloning, origin, and expression of saxitoxin biosynthesis gene sxtB from the toxic dinoflagellate Alexandrium catenella - Han-Sol Kim; Quynh Thi Nhu Bui; Hui Wang; Jang-Seu Ki (Journal of Applied Phycology, 2023)

Comparative transcriptome analysis reveals the molecular mechanism of heat-tolerance in Neopyropia yezoensis induced by Sargassum horneri extract - Qikun Xing; Sol Han; Ji-Sook Park; Charles Yarish; Jang K. Kim (Frontiers in Marine Science, 2023)
Introduction Heat stress is one of the main threats for the seaweed aquaculture, leading to the decay of the blades and causing serious economic losses. A newly developed biostimulant, Sargassum horneri extract (SHE), can enhance the heat-tolerance in Neopyropia yezoensis, which can be applied in the seaweed aquaculture. However, the molecular mechanism underlying this acquired heat-tolerance is still unclear. Method In this study, we examined the transcriptional regulation of N. yezoensis under heat stress after the SHE pre-treatment by performing the RNA-Seq on illumina Novaseq platform and differentially expressed gene analysis. Result and discussion Our results show that, under heat stress, the SHE pre-treatment can alleviate the suppression of genes involved in normal cell activities, such as ribosome biogenesis, photosynthesis, respiration and cell cycle. On the other hand, SHE pre-treatment can also induce some key genes involved in the heat-tolerance. We also found that the combination of SHE pre-treatment and heat stress can induce some genes related to epigenetic modification, suggesting that SHE may facilitate the formation of heat stress memory in N. yezoensis. Our study provides information for understanding the molecular mechanism of heat-tolerance in N. yezoensis and for promoting the application of seaweed-derived biostimulants in the seaweed aquaculture.

Acute toxicity, oxidative stress, and apoptosis due to short-term triclosan exposure and multi- and transgenerational effects on in vivo endpoints, antioxidant defense, and DNA damage response in the freshwater water flea Daphnia magna - Jin-Sol Lee; Yunmoon Oh; Jae-Seong Lee; Hyung Sik Kim (Science of The Total Environment, 2023)

Saxitoxins-producing potential of the marine dinoflagellate Alexandrium affine and its environmental implications revealed by toxins and transcriptome profiling - Han-Sol Kim; Hyunjun Park; Hui Wang; Taehee Kim; Jang-Seu Ki (Marine Environmental Research, 2023)

Statistical discrimination using different machine learning models reveals dissimilar key compounds of soybean leaves in targeted polyphenol-metric metabolomics in terms of traits and cultivation - Chan-Su Rha; Eun Kyu Jang; Jong Suk Lee; Ji-Sung Kim; Min-Ji Ko; Sol Lim; Gun Hwan Park; Dae-Ok Kim (Food Chemistry, 2023)

Advanced technology using supercritical fluid for particle production in pharmaceutical continuous manufacturing - Eun-Sol Ha; Hui-Taek Kang; Heejun Park; Sebin Kim; Min-Soo Kim (Journal of Pharmaceutical Investigation, 2023)

Hypoxia-alleviating hemoglobin nanoclusters for sensitizing chemo-photodynamic therapy of cervical cancer - Han Sol Lee; So-Yeol Yoo; Sang Min Lee; Nae-Won Kang; Sang Kyum Kim; Gyu Yong Song; Dae-Duk Kim; Jae-Young Lee (Chemical Engineering Journal, 2023)

Sargassum horneri and Ascophyllum nodosum extracts enhance thermal tolerance and antioxidant activity of Neopyropia yezoensis - Sol Han; Hye-In Song; Ji-Sook Park; Youn-Jung Kim; Schery Umanzor; Charles Yarish; Jang K. Kim (Journal of Applied Phycology, 2023)

Low salinity causes oxidative stress and modulates specific antioxidant gene expression in the toxic dinoflagellate Alexandrium pacificum - Quynh Thi Nhu Bui; Han-Sol Kim; Jang-Seu Ki (Journal of Applied Phycology, 2022)

Adaptive Formation Control of Multiple Underactuated Autonomous Underwater Vehicles - Ji-Hong Li; Hyungjoo Kang; Min-Gyu Kim; Mun-Jik Lee; Gun Rae Cho; Han-Sol Jin (Journal of Marine Science and Engineering, 2022)
In this paper, we present a 3D formation control scheme for a group of torpedo-type underactuated autonomous underwater vehicles (AUVs). These multiple AUVs combined with an unmanned surface vessel (USV) construct a sort of star-topology acoustic communication network where the USV is at the center point. Due to this kind of topological feature, this paper applies a virtual school concept. This is a geometric graph where each node is taken as a virtual leader for each specific AUV and assigned its own reference trajectory. For each individual vehicle, its formation strategy is simple: just follow the trajectory of its corresponding virtual leader so as for multiple AUVs to compose the given formation. As for the formation subject, this paper mainly focuses on the formation tracking problem rather than the formation producing. For the torpedo-type vehicle considered in this paper, there are only three control inputs (surge force, pitch, and yaw moments) available for its underwater 3D motion and therefore this is a typical underactuated system. For the following vehicle’s trajectory, a sort of potential field method is used for obstacle avoidance, and a neural network-based adaptive scheme is applied to on-line approximate the vehicle’s unknown nonlinear dynamics, and the uncertainty terms including modeling errors, measurement noises, and external disturbances are handled by the properly designed robust scheme. The proposed formation method can guarantee the uniform ultimate boundedness (UUB) of the closed-loop system. Numerical studies are also carried out to verify the effectiveness of the proposed scheme.

Effect of Different Solvents on the Extraction of Compounds from Different Parts of Undaria pinnatifida (Harvey) Suringar - Hyun-Hwa Lee; Jin-Sol Kim; Jun-Han Jeong; Su Mi Park; Ramaraj Sathasivam; Sook Young Lee; Chun Sung Kim (Journal of Marine Science and Engineering, 2022)
Asian kelp (Undaria pinnatifida) is a brown alga mainly grown and consumed in East Asian countries such as China, Japan, and Korea. To date, studies on the various biological activities of Asian kelp have been conducted; however, studies focusing on the different parts of Asian kelp and their use for other than food are limited. Therefore, in this study, different parts of Asian kelp, namely, whole U. pinnatifida (UP), U. pinnatifida blade (UPB), U. pinnatifida stipe (UPS), and U. pinnatifida sporophylls (UPSP), were extracted by using different solvents including ethanol, methanol, and hot water. The antioxidant activity, antiaging effect, and phenolic content of the extracts were investigated. The results revealed that the UPB methanolic extract had significantly higher polyphenol and flavonoid contents, with the respective values of 5.61 mg TAN/g and 7.80 mg QUE/g, than the other extracts. The DPPH and ABTS radical scavenging activities and FRAP values were the highest in the 95% ethanolic (IC50 12.73 mg/mL), methanolic (63.83%), and ethanolic (75.75%) extracts of UPB, respectively. Superoxide dismutase, catalase, and ascorbate peroxidase enzymatic activities were also measured, and the results showed that the activities of these enzymes were higher in the UPB methanolic extract than in the other extracts. Similarly, the highest elastase and tyrosinase inhibitory activity was observed in the UPB methanolic extract. The highest phenolic content was found in the hot water extract of UP (4-hydroxybenzoic acid) and the ethanolic extracts of all parts (naringin and naringenin). The phenolic content of the Asian kelp differed depending on the parts and extraction solvents used. Finally, the antioxidant activity of the UPB extract showed a close correlation with the polyphenol and flavonoid contents. The methanol extract of UPB exhibited excellent antioxidant and antiaging activities, indicating its potential use in the development of functional materials using Asian kelp and in other new applications.

Genomic and transcriptomic analysis of Korean colorectal cancer patients - Sol A Jeon; Ye Jin Ha; Jong-Hwan Kim; Jeong-Hwan Kim; Seon-Kyu Kim; Yong Sung Kim; Seon-Young Kim; Jin Cheon Kim (Genes & Genomics, 2022)
Background Colorectal cancer (CRC) is the third most common type of diagnosed cancer in the world and has the second-highest mortality rate. Meanwhile, South Korea has the second-highest incidence rate for CRC in the world. Objective To assess the possible influence of ethnicity on the molecular profile of colorectal cancer, we compared genomic and transcriptomic features of South Korean CRCs with European CRCs. Methods We assembled a genomic and transcriptomic dataset of South Korean CRC patients (KOCRC; n = 126) from previous studies and European cases (EUCRC; n = 245) selected from The Cancer Genome Atlas (TCGA). Then, we compared the two datasets in terms of clinical data, driver genes, mutational signature, gene sets, consensus molecular subtype, and fusion genes. Results These two cohorts showed similar profiles in driver mutations but differences in the mutation frequencies of some driver genes (including APC, TP53, PABPC1, FAT4, MUC7, HSPG2, GNAS, DENND5B, and BRAF ). Analysis of hallmark pathways using genomic data sets revealed further differences between these populations in the WNT, TP53, and NOTCH signaling pathways. In consensus molecular subtype (CMS) analyses of the study cases, no BRAF mutations were found in the CMS1 subtype of KOCRC, which contrasts with previous findings. Fusion gene analysis identified oncogenic fusion of PTPRK - RSPO3 in a subset of KOCRC patients without APC mutations. Conclusions This study presents insights into the genomic landscape of KOCRCs and reveals some similarities and differences with EUCRCs at the molecular level.

Bacteroides humanifaecis sp. nov., isolated from faeces of healthy Korean - Han Sol Kim; Ji-Sun Kim; Min Kuk Suh; Mi Kyung Eom; Ju Huck Lee; Seung-Hwan Park; Se Won Kang; Dong Ho Lee; Hyuk Yoon; Je Hee Lee; Jung-Sook Lee (Archives of Microbiology, 2022)

Micronization of a poorly water-soluble drug, fenofibrate, via supercritical-fluid-assisted spray-drying - Jeong-Soo Kim; Heejun Park; Kyu-Tae Kang; Eun-Sol Ha; Min-Soo Kim; Sung-Joo Hwang (Journal of Pharmaceutical Investigation, 2022)

Tableting process-induced solid-state polymorphic transition - Heejun Park; Jeong-Soo Kim; Seongwoo Hong; Eun-Sol Ha; Haichen Nie; Qi Tony Zhou; Min-Soo Kim (Journal of Pharmaceutical Investigation, 2022)

Marinobacter arenosus sp. nov., a halotolerant bacterium isolated from a tidal flat - Yunjeong Lee; Veeraya Weerawongwiwat; Jong-Hwa Kim; Min Kuk Suh; Han Sol Kim; Jung-Sook Lee; Jung-Hoon Yoon; Ampaitip Sukhoom; Wonyong Kim (Archives of Microbiology, 2022)

Arenibacterium arenosum sp. nov., isolated from sea sand - Jiseon Jeong; Veeraya Weerawongwiwat; Jong-Hwa Kim; Min Kuk Suh; Han Sol Kim; Jung-Sook Lee; Jung-Hoon Yoon; Ampaitip Sukhoom; Wonyong Kim (Archives of Microbiology, 2022)

Atmospheric river lifecycle characteristics shaped by synoptic conditions at genesis - Sol Kim; John C. H. Chiang (International Journal of Climatology, 2022)
The range of synoptic patterns that North Pacific landfalling atmospheric rivers form under are objectively identified using genesis day 500 hPa geopotential height anomalies in a self‐organizing map (SOM). The SOM arranges the synoptic patterns to differentiate between two groups of climate modes—the first group with ENSO (El Niño Southern Oscillation), PDO (Pacific Decadal Oscillation), PNA (Pacific North American) and NP (North Pacific index) and the second group with AO (Arctic Oscillation), EPO (East Pacific Oscillation), and WPO (West Pacific Oscillation). These two groups have their positive and negative modes organized in opposite corners of the SOM. The ARs produced in each of the synoptic patterns have distinct lifecycle characteristics (such as genesis and landfall location, duration, velocity, meridional/zonal movement) and precipitation impacts (magnitude and spatial distribution). The conditions that favour AR trajectories closer to the tropics tend to produce higher amounts of precipitation. The large‐scale circulation associated with AR genesis shows a close relationship between the genesis location and the location and intensity of the upper‐level jet in the west/central pacific as well as anomalous, low‐level southwesterly winds in the east pacific.

Surface modification strategies for high-dose dry powder inhalers - Heejun Park; Eun-Sol Ha; Min-Soo Kim (Journal of Pharmaceutical Investigation, 2021)

Collinsella acetigenes sp. nov., an Anaerobic Actinobacterium Isolated from Human Feces, and Emended Description of the Genus Collinsella and Collinsella aerofaciens - Kook-Il Han; Ji-Sun Kim; Mi Kyung Eom; Keun Chul Lee; Min Kuk Suh; Han Sol Kim; Seung-Hwan Park; Ju Huck Lee; Se Won Kang; Jam-Eon Park; Byeong Seob Oh; Seoung Woo Ryu; et al. (Current Microbiology, 2021)

Physicochemical analysis techniques specialized in surface characterization of inhalable dry powders - Heejun Park; Eun-Sol Ha; Min-Soo Kim (Journal of Pharmaceutical Investigation, 2021)

Reciprocal Crosses Between Astaxanthin and Capsanthin Rice Unravel Effects of Metabolic Gene Efficacy in Rice Endosperm - Ye Sol Jeong; Jae Kwang Kim; Seung-A. Baek; Jong-Yeol Lee; Dongho Lee; Sun-Hwa Ha (Journal of Plant Biology, 2021)

Comparison between MGI and Illumina sequencing platforms for whole genome sequencing - Sol A. Jeon; Jong Lyul Park; Seung-Jin Park; Jeong Hwan Kim; Sung-Ho Goh; Ji-Youn Han; Seon-Young Kim (Genes & Genomics, 2021)

Lithium enhances exercise-induced glycogen breakdown and insulin-induced AKT activation to facilitate glucose uptake in rodent skeletal muscle - Su-Ryun Jung; Sol-Yi Park; Jin-Ho Koh; Jong-Yeon Kim (Pflügers Archiv - European Journal of Physiology, 2021)
The purpose of this study was to investigate the effect of lithium on glucose disposal in a high-fat diet-induced type 2 diabetes mellitus (T2DM) and streptozotocin-induced type 1 diabetes mellitus (T1DM) animal model along with low-volume exercise and low-dose insulin. Lithium decreased body weight, fasting plasma glucose, and insulin levels when to treat with low-volume exercise training; however, there were no adaptive responses like an increase in GLUT4 content and translocation factor levels. We discovered that lithium enhanced glucose uptake by acute low-volume exercise-induced glycogen breakdown, which was facilitated by the dephosphorylation of serine 473-AKT (Ser473-AKT) and serine 9-GSK3β. In streptozotocin-induced T1DM mice, Li/low-dose insulin facilitates glucose uptake through increase the level of exocyst complex component 7 (Exoc7) and Ser473-AKT. Thus, lithium enhances acute exercise-induced glycogen breakdown and insulin-induced AKT activation and could serve as a candidate therapeutic target to regulate glucose level of DM patients.

Enterococcus faecium L-15 Extract Enhances the Self-Renewal and Proliferation of Mouse Skin-Derived Precursor Cells - Kichul Kim; Sangkyu Park; Hyewon Kim; Sol Min; Seockmo Ku; Jeongmin Seo; Sangho Roh (Probiotics and Antimicrobial Proteins, 2020)

Efficient genome editing using CRISPR–Cas9 RNP delivery into cabbage protoplasts via electro-transfection - Myoung Hui Lee; Jiyoung Lee; Seung A Choi; Ye-Sol Kim; Okjae Koo; Seung Hee Choi; Woo Seok Ahn; Eun Yee Jie; Suk Weon Kim (Plant Biotechnology Reports, 2020)

An overview of chondrosarcoma with a focus on nanoscale therapeutics - Dong Hyun Kim; Han Sol Lee; Yong-Hyeon Mun; SeokJin Koh; Joon-Sun Park; Sang Min Lee; Nae-Won Kang; Mee Yeon Lee; Cheong-Weon Cho; Dae-Duk Kim; Jae-Young Lee (Journal of Pharmaceutical Investigation, 2020)

Comamonas flocculans sp. nov., a Floc-Forming Bacterium Isolated from Livestock Wastewater - Dong-Hyun Kim; Kook-Il Han; Hae-Jun Kwon; Mi-Gyeong Kim; Young-Guk Kim; Doo-Ho Choi; Keun Chul Lee; Min Kuk Suh; Han Sol Kim; Jung-Sook Lee; Jong-Guk Kim (Current Microbiology, 2020)

Functional Characterization of a Novel Oligoalginate Lyase of Stenotrophomonas maltophilia KJ-2 Using Site-Specific Mutation Reveals Bifunctional Mode of Action, Possessing Both Endolytic and Exolytic Degradation Activity Toward Alginate in Seaweed Biomass - Yoo Jung Chu; Hae Sol Kim; Myung Sun Kim; Eun Yeol Lee; Hee Sook Kim (Frontiers in Marine Science, 2020)

Application of diethylene glycol monoethyl ether in solubilization of poorly water-soluble drugs - Eun-Sol Ha; Seon-Kwang Lee; Du Hyung Choi; Seong Hoon Jeong; Sung-Joo Hwang; Min-Soo Kim (Journal of Pharmaceutical Investigation, 2020)

Stability evaluation of H3N2 influenza split vaccine in drying process for solidification - Sung-Jin Kim; Young-Guk Na; Hong-Ki Lee; Hye-Jin Lee; Miao Wang; Hyun Wook Huh; Han-Sol Lee; Jae-Young Lee; Cheong-Weon Cho (Journal of Pharmaceutical Investigation, 2020)

Experimental and Numerical Investigation of Self-Burial Mechanism of Pipeline with Spoiler under Steady Flow Conditions - Woo-Dong Lee; Hyo-Jae Jo; Han-Sol Kim; Min-Jun Kang; Kwang-Hyo Jung; Dong-Soo Hur (Journal of Marine Science and Engineering, 2019)
Herein, hydraulic model experiments and numerical simulations were performed to understand the self-burial mechanism of subsea pipelines with spoilers under steady flow conditions. First, scour characteristics and self-burial functions according to the spoiler length-to-pipe diameter ratio (S/D) were investigated through hydraulic experiments. Further, the Navier–Stokes solver was verified. The experimental values of the velocity at the bottom of the pipeline with a spoiler and the pressure on the sand foundation where the pipeline rested were represented with the degree of conformity. Scour characteristics of a sand foundation were investigated from the numerical analysis results of the velocity and vorticity surrounding the pipelines with spoilers. The compilation of results from the hydraulic experiment and numerical analysis showed that the projected area increased when a spoiler was attached to the subsea pipes. This consequently increased the velocity of fluid leaving the top and bottom of the pipe, and high vorticity was formed within and above the sand foundation. This aggravated scouring at the pipe base and increased the top and bottom asymmetry of the dynamic pressure field, which developed a downward force on the pipeline. These two primary effects acting simultaneously under steady flow conditions explained the self-burial of pipelines with a spoiler attachment.

Discovery of PTE-1, Tourist-like miniature inverted repeat transposable element (MITE), and its activation in transgenic Brassica rapa ssp. pekinensis plants - Sol-ah Kim; YoungJi Jeon; Jee-Soo Park; Young-Doo Park (Horticulture, Environment, and Biotechnology, 2019)

Alteration of Carotenoid Metabolic Machinery by β-Carotene Biofortification in Rice Grains - Hyung-Keun Ku; Ye Sol Jeong; Min Kyoung You; Young Joo Jung; Tae Jin Kim; Sun-Hyung Lim; Jae Kwang Kim; Sun-Hwa Ha (Journal of Plant Biology, 2019)

Shoot Meristem Activity is Involved in Salt Tolerance on Arabidopsis Shoot Growth - Ye Sol Jun; Ok-Kyoung Cha; Jeong Hyun Kim; Horim Lee (Journal of Plant Biology, 2019)

Overexpression of AtYUCCA6 in soybean crop results in reduced ROS production and increased drought tolerance - Jin Sol Park; Hye Jeong Kim; Hyun Suk Cho; Ho Won Jung; Joon-Young Cha; Dae-Jin Yun; Seon-Woo Oh; Young-Soo Chung (Plant Biotechnology Reports, 2019)

Improvement of cellular uptake of hydrophilic molecule, calcein, formulated by liposome - Su-Min Han; Young-Guk Na; Han-Sol Lee; Gi-Ho Son; Seong-Hoon Jeon; Ki-Hyun Bang; Sung-Jin Kim; Hye-Jin Lee; Cheong-Weon Cho (Journal of Pharmaceutical Investigation, 2018)

Root-specific expression of defensin in transgenic tobacco results in enhanced resistance against Phytophthora parasitica var. nicotianae - Hyun-Hwa Lee; Jin-Sol Kim; Quyen T. N. Hoang; Jeong-Il Kim; Young Soon Kim (European Journal of Plant Pathology, 2018)

Human-APOBEC3G-dependent restriction of porcine endogenous retrovirus replication is mediated by cytidine deamination and inhibition of DNA strand transfer during reverse transcription - Sae Young Jin; Hyung Yell Choi; Han Sol Kim; Yong-Tae Jung (Archives of Virology, 2018)

Optimization of TILLING system based on capillary electrophoresis for targeted selection of pepper gene mutants - Han Sol Kang; Sang Hoon Kim; Sang Woo Lee; Se Won Kim; Jaihyunk Ryu; Jin-Baek Kim; Seon-In Yeom; Si-Yong Kang; Yeong Deuk Jo (Horticulture, Environment, and Biotechnology, 2018)

Heat waves in Finland: present and projected summertime extreme temperatures and their associated circulation patterns - Sol Kim; Victoria A. Sinclair; Jouni Räisänen; Reija Ruuhela (International Journal of Climatology, 2018)
The number and intensity of individual hot days affecting Finland in the current and future climate is investigated together with the circulation patterns associated with the hot days. In addition, the number, length and intensity of heat waves lasting at least 3 days is also considered. ERA‐Interim reanalysis data and both direct model output and bias‐corrected data for historical and future climate [representative concentration pathway 4.5 (RCP4.5) scenario] simulations from 17 global climate models are analysed. Three intensities of heat waves and hot days are defined based on daily mean temperature thresholds of 20, 24 and 28 °C. The percentage of summertime days which exceed these temperature thresholds is shown to increase in the future. In ERA‐Interim, 24% of summertime days in southern Finland exceed the lowest temperature threshold while none exceed the highest temperature threshold. Under the RCP4.5 scenario these values increase to 47 and 1%, respectively. Larger relative changes occur in northern Finland. Heat waves are also longer in the RCP4.5 simulations than in the historical simulations. In southern Finland, the mean length of a heat wave where the 20 °C daily mean temperature is exceeded is 6.1 days in the historical simulations but increases to 9.4 days in the RCP4.5 simulations. The hot days in both northern and southern Finland are associated with a statistically significant positive pressure anomaly over Finland and to the east to Finland and a statistically significant negative pressure anomaly over Russia between 90 and 120°E. These pressure anomalies were evident for all intensities of hot days in the current climate and the future climate. The magnitude of the pressure anomalies increases as the daily mean temperature threshold increases. However, for hot days which exceed the same daily mean temperature threshold, the pressure anomalies are weaker in the RCP4.5 simulations than in the historical or ERA‐Interim data.

Decline patterns and risk assessment of 10 multi-class pesticides in young sprout amaranth (Amaranthus mangostanus) under greenhouse growing conditions - In Kyung Kim; Sung-Woo Kim; A. M. Abd El-Aty; Md. Musfiqur Rahman; Md. Humayun Kabir; Han Sol Lee; Hyung Suk Chung; Ji Hoon Jeong; Ho-Chul Shin; Jae-Han Shim (Environmental Science and Pollution Research, 2017)

Dissipation kinetics, pre-harvest residue limits, and hazard quotient assessments of pesticides flubendiamide and fluopicolide in Korean melon (Cucumis melo L. var. makuwa) grown under regulated conditions in plastic greenhouses - Md. Humayun Kabir; A. M. Abd El-Aty; Md. Musfiqur Rahman; Sung-Woo Kim; Han Sol Lee; Hyung Suk Chung; Jung Ah Do; Ji Hoon Jeong; Byung-Joon Chang; Moon Ik Chang; Ho-Chul Shin; Jae-Han Shim (Environmental Science and Pollution Research, 2017)

Desorption of micropollutant from spent carbon filters used for water purifier - Da-Sol Kwon; So-Yeon Tak; Jung-Eun Lee; Moon-Kyung Kim; Young Hwa Lee; Doo Won Han; Sanghyeon Kang; Kyung-Duk Zoh (Environmental Science and Pollution Research, 2017)

Effect of codon optimization on the enhancement of the β-carotene contents in rice endosperm - Ye Sol Jeong; Hyung-Keun Ku; Jae Kwang Kim; Min Kyoung You; Sun-Hyung Lim; Ju-Kon Kim; Sun-Hwa Ha (Plant Biotechnology Reports, 2017)

Selective serotonin reuptake inhibitor sertraline inhibits voltage-dependent K+ channels in rabbit coronary arterial smooth muscle cells - Han Sol Kim; Hongliang Li; Hye Won Kim; Sung Eun Shin; Il-Whan Choi; Amy L Firth; Hyoweon Bang; Young Min Bae; Won Sun Park (Journal of Biosciences, 2016)

Construction of mutation populations by gamma-ray and carbon beam irradiation in chili pepper (Capsicum annuum L.) - Yeong Deuk Jo; Sang Hoon Kim; Ji-Eun Hwang; Ye-Sol Kim; Han Sol Kang; Se Won Kim; Soon-Jae Kwon; Jaihyunk Ryu; Jin-Baek Kim; Si-Yong Kang (Horticulture, Environment, and Biotechnology, 2016)

Development of serological procedures for sensitive, rapid detection of Cucumber mosaic virus in Lilium - Han Sol Kim; Dong Wan Kim; Yong-Tae Jung (Horticulture, Environment, and Biotechnology, 2016)

Evaluating client application status for V-World Open API service - Han-sol Jang; Dong-kyu Kim; Jung-min Kim; In-sung Jang (Spatial Information Research, 2016)

The class III anti-arrhythmic agent, amiodarone, inhibits voltage-dependent K+ channels in rabbit coronary arterial smooth muscle cells - Hongliang Li; Han Sol Kim; Hye Won Kim; Sung Eun Shin; Won-Kyo Jung; Kwon-Soo Ha; Eun-Taek Han; Seok-Ho Hong; Amy L. Firth; Young Min Bae; Il-Whan Choi; Won Sun Park (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Site-Directed Mutagenesis-Based Functional Analysis and Characterization of Endolytic Lyase Activity of N- and C-Terminal Domains of a Novel Oligoalginate Lyase from Sphingomonas sp. MJ-3 Possessing Exolytic Lyase Activity in the Intact Enzyme - Hae Sol Kim; Yu Jeong Chu; Chang-Ho Park; Eun Yeol Lee; Hee Sook Kim (Marine Biotechnology, 2015)

Enhancement of dissolution and bioavailability of ezetimibe by amorphous solid dispersion nanoparticles fabricated using supercritical antisolvent process - Eun-Sol Ha; Jeong-Soo Kim; In-hwan Baek; Sung-Joo Hwang; Min-Soo Kim (Journal of Pharmaceutical Investigation, 2015)

Genetic relationships among diverse spray- and standard-type chrysanthemum varieties and their derived radio-mutants determined using AFLPs - Ye-Sol Kim; Sang Hoon Kim; Sang Yeop Sung; Dong Sub Kim; Jin-Baek Kim; Yeong Deuk Jo; Si-Yong Kang (Horticulture, Environment, and Biotechnology, 2015)

DNA damage and oxidative stress induced by proton beam in Cymbidium hybrid - Yu-Mi Lee; Yeong Deuk Jo; Hyo-Jeong Lee; Ye-Sol Kim; Dong Sub Kim; Jin-Baek Kim; Si-Yong Kang; Sang Hoon Kim (Horticulture, Environment, and Biotechnology, 2015)

KIF1B polymorphisms associated with the risk of inflammatory demyelinating disease in Korean population - Jin Sol Lee; Joon Seol Bae; Byung Lae Park; Hyun Sub Cheong; Jeong-Hyun Kim; Jason Yongha Kim; Ho Jin Kim; Hyoung Doo Shin (Genes & Genomics, 2014)

Spirosoma radiotolerans sp. nov., a Gamma-Radiation-Resistant Bacterium Isolated from Gamma Ray-Irradiated Soil - Jae-Jin Lee; Sathiyaraj Srinivasan; Sangyong Lim; Minho Joe; Seonghun Im; So Il Bae; Kyoung Ryun Park; Ji-Hee Han; Se-Hee Park; Bo-min Joo; Sol-Ji Park; Myung Kyum Kim (Current Microbiology, 2014)

Production and characterization of soluble human TNFRI-Fc and human HO-1(HMOX1) transgenic pigs by using the F2A peptide - Sol Ji Park; Bumrae Cho; Ok Jae Koo; Hwajung Kim; Jung Taek Kang; Sunghoon Hurh; Su Jin Kim; Hye Jung Yeom; Joonho Moon; Eun Mi Lee; Ji Yei Choi; Ju Ho Hong; et al. (Transgenic Research, 2014)

Effect of cardiorespiratory fitness on acute inflammation induced increases in arterial stiffness in older adults - Sae Young Jae; Eun Sun Yoon; Soo Jin Jung; Sol Gi Jung; Soo Hyun Park; Byung Sung Kim; Kevin S. Heffernan; Bo Fernhall (European Journal of Applied Physiology, 2013)

Expression of the Human Tissue-Plasminogen Activator in Hairy Roots of Oriental Melon (Cucumis melo) - Sol Kang; Hemavathi Ajjappala; Hyun-Hui Seo; Joon-Soo Sim; Sang-Hong Yoon; Bon-Sung Koo; Yong-Hwan Kim; Sukchan Lee; Bum-Soo Hahn (Plant Molecular Biology Reporter, 2011)

A possible association of EMID2 polymorphisms with aspirin hypersensitivity in asthma - Charisse Flerida A. Pasaje; Jeong-Hyun Kim; Byung-Lae Park; Hyun Sub Cheong; Mi-Kyeong Kim; Inseon S. Choi; Sang Heon Cho; Chein-Soo Hong; Yong Won Lee; Jae-Young Lee; In Song Koh; Tae-Joon Park; et al. (Immunogenetics, 2011)